Local access network technologies - France, P. W. (Institution of Engineering and Technology, 2004)
The work presented in this book reviews the major new access technologies that are finding their way into significant use. The book is a compilation of chapters written by several contributors, all of whom have extensive experience in the field and are internationally recognised for their work. By and large, the authors are based or associated with BT's development facilities, now known as BT Exact, at Adastral Park, near Ipswich in the UK. The first chapter is a general introduction to access networks, and overviews the major new technologies and their use by network operators. Chapter 2 examines market trends for narrowband and broadband applications, gives some indication of bandwidths required, and describes the access bottleneck. Chapters 3, 4, 5, 6 and 7 then discuss aspects of copper technologies including ADSL and VDSL, but also including 'local loop unbundling' and 'frequency planning'. In particular, Chapter 5 describes how ADSL has been used in the broadband programme and discusses many of the operational issues such as increasing coverage into rural areas. Chapters 8, 9 and 10 then cover optical fibre technologies, outlining the different topologies in use today, discussing both PONs and point-to-point technologies in some depth, as well as the physical infrastructure issues of fibre-to-the-home. Chapters 11, 12, 13 and 14 move on to radio technologies, from wireless LANs and fixed radio technologies through to satellite and UMTS systems. The large scale deployment of cable systems warrants a specific chapter on this topic, Chapter 15, which describes not only cable technology and means for delivering TV and voice, but also covers the DOCSIS standard for data (and Internet) delivery using cable modems. Chapter 16 discusses the increasing use of SDK in the access network. Finally, Chapter 17 discusses management of the access network, based on TMN architecture, and presents many of the issues concerned with network management of broadband access.